Attitudes of pharmacy students towards patient safety: a cross-sectional study from six developing countries - Abdallah Y Naser; Hassan Alwafi; Zahra Khalil Alsairafi; Ahmed Awaisu; Oriana Awwad; Eman Zmaily Dahmash; Salman Hussain; Hamad S Alyami; Alaa Alsharif; Avinash Kumar Singh; Fatima B Jeragh-Alhaddad; Angga Prawira Kautsar; et al. (BMJ Open)
Objective To evaluate the attitudes of undergraduate pharmacy students towards patient safety in six developing countries.Design A cross-sectional study.Setting Participants were enrolled from the participating universities in six countries.Participants Undergraduate pharmacy students from the participating universities in six developing countries (Jordan, Saudi Arabia, Kuwait, Qatar, India and Indonesia) were invited to participate in the study between October 2018 and September 2019.Primary outcome Attitudes towards patient safety was measured using 14-item questionnaire that contained five subscales: being quality-improvement focused, internalising errors regardless of harm, value of contextual learning, acceptability of questioning more senior healthcare professionals’ behaviour and attitude towards open disclosure. Multiple-linear regression analysis was used to identify predictors of positive attitudes towards patient safety.Results A total of 2595 students participated in this study (1044 from Jordan, 514 from Saudi Arabia, 134 from Kuwait, 61 from Qatar, 416 from India and 429 from Indonesia). Overall, the pharmacy students reported a positive attitude towards patient safety with a mean score of 37.4 (SD=7.0) out of 56 (66.8%). The ‘being quality-improvement focused’ subscale had the highest score, 75.6%. The subscale with the lowest score was ‘internalising errors regardless of harm’, 49.2%. Female students had significantly better attitudes towards patient safety scores compared with male students (p=0.001). Being at a higher level of study and involvement in or witnessing harm to patients while practising were important predictors of negative attitudes towards patient safety (p<0.001).Conclusion Patient safety content should be covered comprehensively in pharmacy curricula and reinforced in each year of study. This should be more focused on students in their final year of study and who have started their training. This will ensure that the next generation of pharmacists are equipped with the requisite knowledge, core competencies and attitudes to ensure optimal patient safety when they practice.